2014
DOI: 10.3748/wjg.v20.i18.5320
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for nonalcoholic fatty liver disease: New challenges and new opportunities

Abstract: Nonalcoholic fatty liver disease (NAFLD) is becoming rapidly one of the most common indications for orthotopic liver transplantation in the world. Development of graft steatosis is a significant problem during the post-transplant course, which may happen as a recurrence of pre-existing disease or de novo NAFLD. There are different risk factors that might play a role in development of graft steatosis including post-transplant metabolic syndrome, immune-suppressive medications, genetics and others. There are few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 0 publications
1
99
0
Order By: Relevance
“…177 It is expected that NAFLD may become the major reason for living-donor transplantation in the United States by 2030. 178 Although bariatric surgery is currently recognized as the standard treatment option for morbid obesity and its related comorbidities, the number of operations performed is far from sufficient to meet the need for intervention. In fact, less than 500,000 bariatric surgery procedures are performed worldwide every year today.…”
Section: 176mentioning
confidence: 99%
“…177 It is expected that NAFLD may become the major reason for living-donor transplantation in the United States by 2030. 178 Although bariatric surgery is currently recognized as the standard treatment option for morbid obesity and its related comorbidities, the number of operations performed is far from sufficient to meet the need for intervention. In fact, less than 500,000 bariatric surgery procedures are performed worldwide every year today.…”
Section: 176mentioning
confidence: 99%
“…Metagenomics have also identified lung adapted strains of atypical bacteria suggesting novel pathogens (15). Metagenomics and metatranscriptomics have also identified novel metabolic functions in the CF airway that form a metabolic link between Streptococcus and both Pseudomonas and Rothia (25,26). The CF airway hosts a diverse microbial community that we are just beginning to elucidate.…”
Section: Results/conclusionmentioning
confidence: 99%
“…For example, intestinal translocation of specific microbiota in mice, and the detection of specific microbiota in people, are associated with the development of non-alcoholic fatty liver disease and steatohepatitis, common precursors to hepatic fibrosis (22)(23)(24), and common indications for liver transplant in adults (25). Studies in mice have also demonstrated that CFTR dysfunction can predispose to liver fibrosis (26).…”
Section: S51 Cf Liver Disease: Clinical Presentations and Definitionsmentioning
confidence: 99%
“…The pathogenesis of NAFLD has not been fully understood, but it is observed that obesity, diabetes and hyperlipidemia are the major risk factors which are associated with development of non-alcoholic fatty liver disease [4,5,6]. NAFLD is most prevalent disease in developed [7] as well as in developing countries. In India the prevalence rate of NAFLD is 9-32% in among population [8].…”
Section: Introductionmentioning
confidence: 99%